(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
Pumpkin (Cucurbita maxima spp.), a member of the gourd family Cucurbitaceae, is typically characterised by a hard orange rind with distinctive grooves. Pumpkin is a nutrient-dense fruit that offers numerous health benefits. However, studies on functional foods, such as sugar free pumpkin spread, remain limited in Malaysia. Therefore, this study aimed to determine the physicochemical properties and sensory evaluation of sugar free pumpkin spreads prepared with different sweeteners. Four formulations were developed i.e. pumpkin spread with sugar as a control (PSc), pumpkin spread with allulose sweetener (PSa), pumpkin spread with monk fruit sweetener (PSm) and pumpkin spread with stevia sweetener (PSs). Proximate analysis, total soluble solid, pH, texture and sensory analysis were conducted on all formulations. The results showed that PSa, PSm, and PSs had moisture contents of 27.72%, 27.34% and 26.13%, respectively, which were significantly lower than PSc (46.68%). For ash content, the highest value was recorded in PSs (6.53%), which also had the highest protein (6.57%) and fat content (4.76%). Meanwhile, the highest fibre content was found in PSm formulation (5.92%). However, the pH value for all samples showed no significant difference, ranging from 6.41 to 6.43. While the total soluble solid (TSS) showed a significant difference, PSc recording the highest TSS value (44.88 oBrix) compared to the other formulations. For sensory evaluation, the analysis found that the most preferred formulation was PSc, followed by PSa, PSm, and PSs. These findings demonstrated the potential of alternative sweeteners in developing sugar-free pumpkin spreads, offering a functional and healthier option with highly acceptable sensory attributes.